Health expenditure and child health outcomes in Sub-Saharan Africa (2017)
This study sought to understand the relationship between child health outcomes and health spending while investigating lagged effects. The study employed panel data from 45 Sub-Saharan African countries between 1995 and 2011 obtained from the World Bank’s World Development Indicators. Fixed and Random effect models were estimated. Under-five, infant and neonatal mortality were used as child health outcomes while total health spending. The effects of one and two period lags of expenditure were estimated. The results show a positive and significant relationship between health expenditure and child health outcomes with elasticities of -0.11 for infant mortality, -0.15 (under-five mortality) and -0.-8 (ne0natal mortality). Public health expenditure. Positive and significant lagged effects were also estimated between health expenditure and child health. The findings suggests that, while health expenditure is crucial for the improvement of child health, it is equally important for this expenditure to be sustainable as it has delayed effects.